Dietary Probiotic Supplementation Suppresses Subclinical Necrotic Enteritis in Broiler Chickens in a Microbiota-Dependent Manner - Zhao, Ying; Zeng, Yan; Zeng, Dong; Wang, Hesong; Sun, Ning; Xin, Jinge; Zhou, Mengjia; Yang, Hanbo; Lei, Lei; Ling, Hongli; Khalique, Abdul; Rajput, Danish Sharafat; et al. (Frontiers in Immunology, 2022)
Background: Poultry production is one of the most consumed meat worldwide and develops rapidly. Reducing antibiotic usage results in the outbreak of subclinical necrotic enteritis (SNE) again and influences global poultry production. Probiotics can be used as a potential alternative to antibiotics to prevent SNE. However, the precise mechanism of probiotics action and which gut microbes confer this efficacy remain elusive. Methods and results: The subclinical necrotic enteritis animal model was used to reveal the mechanism of probiotics on intestinal health by RNA Sequencing and 16S rDNA amplicon sequencing. H2 (Bacillus licheniformis H2) feeding significantly reduced the relative abundance of C. perfringens in the ileum and markedly ameliorated the pathological damage of ileum and liver. Moreover, oral administration of H2 contributed to enhancing intestinal barrier function and epithelial renewal, reducing energy consumption, and improving nutrient absorption in the intestine. Probiotic H2 also ameliorated the inflammatory response and increased immunity to SNE-infected broilers. Finally, H2 feeding regulated liver gene expression to suppresses immune response and promotes growth and metabolism rely on the gut microbiota. Conclusions: These results reported the mechanism of probiotics H2 action in maintaining the gut health and thus promoting growth, and H2 may serve as an antibiotic alternative for preventing SNE in poultry farming.